Effect of eHealth cardiac rehabilitation on health outcomes of coronary heart disease patients: A systematic review and meta‐analysis. (3rd February 2020) - Su, Jing Jing; Yu, Doris Sau Fung; Paguio, Jenniffer Torralba
Abstract: Aims: To evaluate the effects of eHealth cardiac rehabilitation (CR) on health outcomes of coronary heart disease patients and to identify programme design, which may lead to more effective health benefits. Design: A systematic review and meta‐analysis following Cochrane Handbook for Systematic Reviews of Interventions . Data sources: Medline, EMBASE, CLNAHL, Web of Science, Scopus, PsycINFO, Cochrane Central Register of Controlled Trails, PubMed and CNKI were searched over the period from 1806 to April 2019. Review methods: A systematic review and meta‐analysis of randomized controlled trials to examine the effect of eHealth CR on health outcomes of coronary heart disease patients. We used RevMan 5.3 for risk of bias assessment and meta‐analysis and GRADE software for generating findings. Results: In all, 14 trials with 1, 783 participants were included. eHealth CR has significantly promoted duration of physical activity, daily steps, quality of life (QoL) and re‐hospitalization. Using comparative analysis of programme design elements, including mode of delivery, intervention content, motivational strategies and social support, between the effective and ineffective eHealth CR, it was found that comprehensive empowerment strategies and follow‐up care by tele‐monitoring may be the crucial characteristics leading to more favourable treatment effect. Conclusion: eHealth CR is effective in engaging patients in active lifestyle, improving QoL and reducing re‐hospitalization. Future research needs to test the effects of comprehensive CR programmes by incorporating empowerment strategies and tele‐monitoring as active components. Impact: eHealth has been increasingly applied to increase accessibility and uptake of CR. Integrative evidence to indicate its effects on health outcomes is lacking. This review identified its positive effects on some behavioural, psychosocial and health service use outcomes. Together with insights about which programme design elements may positively shape the outcomes, this review informs the role and practice of cardiovascular nurses in promoting evidence‐based eHealth CR. Abstract : 目的: 评价电子医疗心脏康复(CR)对冠心病患者健康结果的影响, 并确定方案设计, 以期带来更为有效的健康效益。 设计: 根据《干预措施系统评估科克兰手册》开展系统评估与荟萃分析。 数据来源: 通过Medline、EMBASE、CLNAHL、Web of Science、Scopus、PsycINFO、Cochrane 临床对照试验中心注册数据库、PubMed和中国知网数据库对1806年至2019年4月期间的文献进行检索。 评估方法: 针对随机对照试验展开系统评估与荟萃分析, 以研究电子医疗心脏康复对冠心病患者健康结果的影响。我们采用RevMan 5.3进行偏倚风险评估以及荟萃分析, 同时应用GRADE软件生成发现结果。 结果: 共纳入了14项试验, 涉及1, 783名受试者。电子医疗心脏康复可显著地提高体力活动时间、日常生活步数、生活质量(QoL)和再入院情况。通过对有效和无效电子医疗心脏康复之间的方案设计要素, 包括释药行为、干预内容、激励策略和社会支持进行比较分析, 结果发现综合授权策略以及远程监测的后续护理可能对产生更为有利的治疗效果起决定作用。 结论: 电子医疗心脏康复可有效促使患者积极运动, 提高生活质量, 降低再住院率。今后的研究需将增强能力战略和远程监测作为有效方式来测试综合心脏康复方案的效果。 影响: 电子医疗已不断应用于增加心脏康复的可及性和摄取量。尚无综合证据表明其对健康结果的影响。本次评估确定了其对某些行为、心理社会和卫生服务使用结果的积极影响。结合针对何种方案设计要素可能对结果产生积极影响的研究发现, 本次评估说明了对心血管护士在促进循证电子医疗心脏康复方面的作用和实践。